Optimization of High-Crowd-Density Facilities Based on Discrete Event Simulation - M. Alginahi, Yasser; N. Kabir, Muhammad; Mohamed, Ali I. (Malaysian Journal of Computer Science, 2013)
Crowd modelling and simulation has been utilized over the last few decades to study crowd behaviour, estimate evacuation time, and assess safety requirements. In this study, the flow of people in and out of public utilities (washrooms) of a highly populated mosque is simulated. A typical washroom consists of four underground levels located outside the mosque building and can be accessed using staircases or escalators. To study the effect of crowd flow in and out of the washroom during peak times, a new model is built according to the access characteristics to each level. The model is based on Discrete Event Simulation (DES) approach. DES provides the crowd flow behaviour and optimization is performed based on the simulation to obtain the optimized washroom facility to serve the population. The simulation results shows that during peak times when the number of people visiting Haram could reach one-million; the washroom units of the Haram could serve up to about 11.6% of this population. However, the optimization results, given the current washroom layouts, show that if the number of toilets and ablution places are increased by a factor 1.2 the total number of people served would increase to 12.35%. This result is used to make some recommendations which can be further implemented for better layout arrangements, evacuation planning during emergency and public awareness on safety aspects.